Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. High cliffs forming southern terminal of mts. [mountains] which have formed eastern side of Kjerulfs [Kjerulf] Fjord. Photo taken on southern slope, looking N.N.W. This is No. 26 in pan C.